Efficacy of Drainless Total Thyroidectomy in Intrathyroidal Lesions of Thyroid - Battoo,Azhar Jan (2018)
Abstract Introduction There is difference of opinion about the placement of the drain in thyroid surgeries, and, to the best of our knowledge, the efficacy of drainless total thyroidectomy regarding various parameters of thyroid lesions has not been well-established. Objective To report our experience with drainless total thyroidectomy, and to define an appropriate patient population for its performance. Methods This is a retrospective case analysis of the patients who underwent total thyroidectomy for intrathyroidal lesions with or without central neck dissection in a tertiary referral hospital (number = 74). The patients, who had undergone total thyroidectomy without any drain insertion, were analyzed, and the relationships among various parameters of thyroid lesions were noted in relation to seroma and hematoma formation. Results Seroma formation was noted only in 5 out of 74 patents (6.75%). All of the seromas that occurred were observed in patients with thyroid lesions < 4 cm, and 4 out of 5 seromas were observed in patients with a malignant pathology. There was no statistically significant difference in seroma formation between patients younger or older than 50 years of age. The nature of the lesion, whether benign or malignant, did not affect the formation of seroma. Of interest is the fact that none of the 10 patients who had central neck dissection performed as part of their treatment developed seroma. Conclusions Drainless total thyroidectomy is safe across all age groups for patients harboring either benign or malignant thyroid pathologies. However, caution is to be observed in opting for drainless total thyroidectomy in patients with large lesions (> 5 cm)